Concurrent engineering approach in the development of natural fibre metal laminate product : Case study on car front hood - Mohd Ishak, Noordiana (2019)
This thesis explores the solutions to improve fuel efficiency towards achieving the reduction in CO2 emissions by utilizing the natural fibre metal laminate (nFML) as car front hood. Fibre metal laminate (FML) is a lightweight material that inherits advantages of metal and fibre reinforced composite which have outstanding physical and mechanical properties compared with monolithic metal structures. To date, very little research has been reported related to nFML. This research involved concurrent engineering approach in material selection for nFML car front hood using Fuzzy VIKOR method, generated inventive solutions through Theory of Inventive Problem Solving (TRIZ) method and investigated the formability and water absorption behaviour of the nFML to satisfy the intended product design specifications (PDS). Kenaf fibre and polypropylene have been identified as the suitable natural fibre and thermoplastic matrix for fabrication of the nFML using Fuzzy VIKOR method for the car front hood. Identification of problems or contradictions of nFML as car front hood system was constructed using TRIZ method; two layers of kenaf woven fibre [0º/90º] reinforced composite has been identified as the optimal stacking configuration for the reinforced composite in nFML. Forming analysis was conducted to determine the maximum forming limit of the nFML during stamping. Hemispherical punch test was carried out to determine the formability and circle grid analysis was used to determine the forming limit diagram (FLD) and failure limit curve (FLC) of the nFML. Range of safety, critical zone where necking and fracture will occur and strain level of the nFML were also plotted in the FLD. The graph revealed that the nFML have a potential to be formed into a complex shapes compared to aluminium sheet. The nFML also able to sustain higher strain before failure showing that the nFML structure can have the potential for better formability characteristics than aluminium sheet. A further analysis of nFML were conducted to determine the water absorption behaviour of the nFML to further study the function analysis in TRIZ method, the humidity caused by rain or mist is one of the main contradiction in order to perform the nFML as car front hood. Besides water absorption and thickness swelling, tensile test was also conducted to determine the effect of water to nFML strength. It is observed that the moisture content has effect on the tensile properties but the nFML has minimal effect on water absorption behaviour. The developed nFML car front hood is 85% lighter and 96% cheaper than steel. This thesis contributes to the current research by identifying the potential of the nFML in the development of automotive components. This research has successfully demonstrated the capability of nFML in the design of car front hood that satisfies the intended PDS through concurrent engineering approach.